Exploring one health-based strategies for rabies elimination: Overview and future prospects. - Renyun Zha; Jianyun Lu; Jianying Chen; Cheng Guo; Jiahai Lu (PLoS Neglected Tropical Diseases)
Background Establishing a comprehensive and coordinated mechanism for rabies management is essential for achieving the goal of eliminating the disease. It requires the involvement of multiple disciplines and departments, as well as the implementation of necessary policies and measures. The recent COVID-19 pandemic has added further challenges to the goal, particularly for developing countries like China. However, certain regions in China are leveraging local advantages and departmental strengths to actively explore effective strategies. Principal findings This review provides an overview of the global prevalence of rabies, international cooperation efforts, and specific measures. Of particular significance is the analysis of the transformation of the rabies situation in China as well as an exemplar management of a rabies case in the Baiyun District of Guangzhou, Guangdong Province. We also discuss the hopeful action plan based on the One Health concept, aimed at achieving the goal of rabies elimination by 2030. Conclusions Rabies remains a significant threat to public health and economies across most countries worldwide. Despite this, eliminating rabies is increasingly feasible, with China showcasing notable progress, including the adoption of the One Health approach in disease prevention and control strategies. Synopsis The distinction between disease eradication and elimination lies in their scope and permanence. Eradication involves globally reducing the incidence of infection caused by a specific agent to zero, requiring no further intervention measures once achieved. In contrast, disease elimination focuses on reducing the incidence of infection within a specific geographic area to zero, necessitating ongoing actions to prevent its transmission or re-emergence. In the long history of humans' battle against infectious diseases, the complete eradication of smallpox has undoubtedly been an inspiring achievement. However, emerging and re-emerging infectious diseases have remained in the forefront of people's minds, causing significant morbidity, mortality, and potential economic burdens in impoverished countries and regions worldwide. It is disappointing that rabies has not been eradicated globally. While high-income countries have achieved the elimination of canine-mediated rabies through dog vaccination and population management programs, there are fewer examples of successful large-scale elimination of canine rabies in low- and middle-income countries, primarily limited to Latin America.